Effect Of Malathion And Fungicide Ridomil On Root Growth Of Allium Cepa L. - Noori, Aveen M.; Ertushi, Ali H. (Technium BioChemMed, 2021)
The harmful effects of the active ingredient malathion and the fungicide ridomil on Allium cepa L. were studied in this research. We employed the percentage of germination, length of root, weight gain, and other factors to achieve this goal. The results revealed substantial Weight increase, germination percentage, and root length have all changed. The study’s focus was to assess the toxic impact of malathion pesticide and fungicide ridomil on root growth. Allium cepa germination percentage, root length, and gaining weight were measured after they were subjected to a variety of dosages of malathion and fungicide ridomil (0.0,0.25, 0.5, 1.0, and 2.0, mgL-1) for 12 days. Subsequently the root development Both malathion and fungicide ridomil concentrations were inversely associated at all times when you’re exposed,according to the obtained results.